Compression Speed Enhancements to LZO for Multi-core Systems - Kane, Jason; Yang, Qing (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2012)
This paper examines several promising throughput enhancements to the Lempel-Ziv-Oberhumer (LZO) 1x-1-15 data compression algorithm. Of many algorithm variants present in the current library version, 2.06, LZO 1x-1-15 is considered to be the fastest, geared toward speed rather than compression ratio. We present several algorithm modifications tailored to modern multi-core architectures in this paper that are intended to increase compression speed while minimizing any loss in compression ratio. On average, the experimental results show that on a modern quad core system, a 3.9x speedup in compression time is achieved over the baseline algorithm with no loss to compression ratio. Allowing for a 25% loss in compression ratio, up to a 5.4x speedup in compression time was observed.